2011
DOI: 10.3109/02699052.2011.558038
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the diffusion tensor imaging properties of the corpus callosum in acute and chronic diffuse axonal injury

Abstract: The diffusion properties of the corpus callosum correlated with clinical outcome in this longitudinal investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 39 publications
2
27
0
2
Order By: Relevance
“…Conversely, deterioration of white matter microstructure in the first 6 months after injury has been associated with worse clinical outcome (Ljungqvist et al, 2011). …”
Section: White Matter Injury As a Marker Of Tbi Outcomementioning
confidence: 99%
“…Conversely, deterioration of white matter microstructure in the first 6 months after injury has been associated with worse clinical outcome (Ljungqvist et al, 2011). …”
Section: White Matter Injury As a Marker Of Tbi Outcomementioning
confidence: 99%
“…2 The corpus callosum (CC) is particularly vulnerable to diffuse axonal injury. 3,4,5,6,7 There are conflicting results on the relation between acute injury severity and the persistence of CC injury.…”
Section: Event-related Potential Measure Of Interhemispheric Transfermentioning
confidence: 99%
“…Longitudinal studies have shown decreased FA in the acute phase and then decreased FA and increased MD in the chronic phase, which is suggestive of axonal injury followed by demyelination or gliosis. 84,85 MacDonald and colleagues described FA reductions in 38 of 63 U.S. military personnel with blast-related mTBI, as well as increased MD on the initial scan in the subacute time frame, then normalized MD on the follow-up scan at 6 to 12 months, which was suggestive of resolved edema and inflammation. 36 This finding does not contradict previously described reports of increased MD from demyelination or gliosis in the chronic time frame, as those studies included patients with moderate and severe TBI.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%